Advances of MnO2 nanomaterials as novel agonists for the development of cGAS-STING-mediated therapeutics - Zhang, Tangxin; Hu, Chunmiao; Zhang, Wenting; Ruan, Yongdui; Ma, Yuhe; Chen, Dongsheng; Huang, Yuhe; Fan, Shuhao; Lin, Wensen; Huang, Yifan; Liao, Kangsheng; Lu, Hongemi; et al. (Frontiers in Immunology, 2023)
As an essential micronutrient, manganese plays an important role in the physiological process and immune process. In recent decade, cGAS-STING pathway, which can congenitally recognize exogenous and endogenous DNA for activation, has been widely reported to play critical roles in the innate immunity against some important diseases, such as infections and tumor. Manganese ion (Mn2+) has been recently proved to specifically bind with cGAS and activate cGAS-STING pathway as potential cGAS agonist, however, is significantly restricted by the low stability of Mn2+ for further medical application. As one of the most stable forms of manganese, manganese dioxide (MnO2) nanomaterials have been reported to show multiple promising functions, such as drug delivery, anti-tumor and anti-infection activities. More importantly, MnO2 nanomaterials are also found to be a potential candidate as cGAS agonist by transforming into Mn2+, which indicates their potentials for cGAS-STING regulations in different diseased conditions. In this review, we introduced the methods for the preparation of MnO2 nanomaterials as well as their biological activities. Moreover, we emphatically introduced the cGAS-STING pathway and discussed the detailed mechanisms of MnO2 nanomaterials for cGAS activation by converting into Mn2+. And we also discussed the application of MnO2 nanomaterials for disease treatment by regulating cGAS-STING pathway, which might benefit the future development of novel cGAS-STING targeted treatments based on MnO2 nanoplatforms.